Adaptive ultra‐hypofractionated whole‐pelvic radiotherapy in high‐risk and very high‐risk prostate cancer on 1.5‐Tesla MR‐Linac: Estimated delivered dose and early toxicity results - Linrui Gao; Ran Wei; Shirui Qin; Yuan Tian; Wenlong Xia; Yongwen Song; Shulian Wang; Hui Fang; Yu Tang; Hao Jing; Yueping Liu; Yuan Tang; et al. (Chronic Diseases and Translational Medicine, 2024)
Abstract Background Magnetic resonance (MR)‐guided ultra‐hypofractionated radiotherapy with whole‐pelvic irradiation (UHF‐WPRT) is a novel approach to radiotherapy for patients with high‐risk (HR) and very high‐risk (VHR) prostate cancer (PCa). However, the inherent complexity of adaptive UHF‐WPRT might inevitably result in longer on‐couch time. We aimed to estimate the delivered dose, study the feasibility and safety of adaptive UHF‐WPRT on a 1.5‐Tesla MR‐Linac. Methods Ten patients with clinical stage T3a‐4N0‐1M0‐1c PCa, who consecutively received UHF‐WPRT, were enrolled prospectively. The contours of the target and organ‐at‐risks on the position verification‐MR (PV‐MR), beam‐on 3D‐MR(Bn‐MR), and post‐MR (after radiotherapy delivery) were derived from the pre‐MR data by deformable image registration. The physician then manually adjusted them, and dose recalculation was performed accordingly. GraphPad Prism 9 (GraphPad Prism Software Inc.) was utilized for conducting statistical analyses. Results In total, we collected 188 MR scans (50 pre‐MR, 50 PV‐MR, 44 Bn‐MR, and 44 post‐MR scans). With median 59 min, the mean prostate clinical target volume (CTV)‐V100% was 98.59% ± 2.74%, and the mean pelvic CTVp‐V100% relative percentages of all scans was 99.60% ± 1.18%. The median V29 Gy change in the rectal wall was −2% (−18% to 20%). With a median follow‐up of 9 months, no patient had acute Common Terminology Criteria for Adverse Events (CTCAE) grade 2 or more severe genitourinary (GU) or gastrointestinal (GI) toxicities (0%). Conclusion UHF‐RT to the prostate and the whole pelvis with concomitant boost to positive nodes using an Adapt‐To‐Shape (ATS) workflow was technically feasible for patients with HR and VHR PCa, presenting only mild GU and GI toxicities. The estimated target dose during the beam‐on phase was clinically acceptable based on the 3D‐MR–based dosimetry analysis. Clinical trial registration Chinese Clinical Trial Registry ChiCTR2000033382.